Recent Advances in Regional Anaesthesia: A Comprehensive Review - Baby, Alunia Mary; Jishnuraj; Vishnu M.G (Jurnal Vokasi Kesehatan, 2024)
Regional anaesthesia has revolutionized modern practice in anaesthesia, and the review will focus on recent technological and procedural developments, with special emphasis on efficacy, safety profiles, and impact on patient outcomes. Recent developments, especially with the integration of ultrasound-guided techniques, have substantially enhanced procedural precision and safety and made possible substantial reductions in opioid requirements. Evidence indicates that such developments bring improved pain control into recovery results in comparison with the traditional general anaesthesia methods. The latter still modulates regional anaesthesia training and implementation through current technological developments and standard teaching methods but still presents problems in standardization of techniques and access. These advances will greatly influence perioperative care, making potentially for shorter stays and improved rehabilitation for patients, with maximum satisfaction through optimal pain management protocols.